Pengaruh Pembelajaran Berbasis Pendekatan Saintifik dan Lingkungan Sekolah sebagai Sumber Belajar IPA Terhadap Penguasaan Konsep dan Keterampilan Proses Siswa Kelas IV - Yahanan; Irwan Koto; Puspa Djuwita (UNIB Press, 2023)
This study aims to (1) explain the implementation of science learning using a scientific approach and utilization of the school environment. (2) determine the effect of a scientific approach and utilization of the school environment on the mastery of science concepts in fourth grade students. (3) to determine the effect of a scientific approach and the use of the school environment on science process skills in grade IV students. This type of research is quasi-experimental research or quasi-experimental. The design used in this study was a control group pre-test- post-test design. The subjects in this study were all fourth grade students at SD Negeri Muara Kulam for the 2022/2023 academic year. The results of observations on the implementation of learning at the first meeting obtained a percentage of the experimental class 68% then the control class 62%, for the second meeting the average results of the experimental class learning implementation were 93% and the control class 86%. The average value of students' process skills at the first meeting in the experimental class was 79.7%, while in the control class it was 64.6%. The average value of the results of observations of science process skills at the second meeting in the experimental class was 84.8%, while in the control class it was 74.6%. The results of the t-test analysis show that the value of Sig = 0.000 <0.05. In accordance with the test criteria, then Ha is accepted and Ho is rejected. So it can be concluded that there is an effect of learning using a scientific approach to mastery of the concepts of fourth grade students at SD Negeri Muara Kulam.